Tarkib Nama-Nama Hari Kiamat Pada Juz ‘Amma - Aldi Ramdani; Abdurrahman Abdurrahman (UIN Sunan Gunung Djati Bandung, 2023)
Juz 'Amma is a section of the Quran that is commonly read by Muslims, and many people start their Quranic learning and memorization journey with Juz 'Amma. To better understand the meanings of the verses in Juz 'Amma, it is important to be familiar with the grammatical structures. The aim of this research is to simplify the understanding and provide a broader insight into the grammatical structures in Juz 'Amma. This research was conducted using a qualitative research approach and relied on the method of extracting information from literary sources. Based on the research findings, there are twenty-seven names for the Day of Judgment in the entire Quran, and nineteen verses in Juz 'Amma. These structures are divided into three categories: compound structures with twelve names, single structures with three names, and compound descriptive structures with four names.